Peran Dan Manfaat Kurikulum Merdeka Dalam Meningkatkan Kualitas Pembelajaran Di Jenjang Sekolah Dasar - Aisyah Wardatun Nisa; Eka Titi Andaryani (CV. Alim's Publishing, 2023)
As we already know, the independent curriculum is a new curriculum that is currently being published. From year to year, the educational curriculum is increasingly undergoing changes, these changes are adapted to technological developments and developments in this new industrial era. Approximately 2 years ago, in the pandemic era or Covid-19 era, the curriculum that applied in schools was the 2013 curriculum and the prototype curriculum. The prototype curriculum is a curriculum that develops progress from the 2013 curriculum, where the curriculum is referred to as the emergency curriculum for the 2022 and 2023 school years. At that time the government established the Merdeka curriculum for all schools deemed ready to implement this curriculum, various technical guidance that is currently needed for school principals as well as teachers and educational staff in implementing the Merdeka curriculum, it can be implemented through technical guidance, which is carried out online. This online guidance is expected to be able to make participants comfortable and more motivated to continue following or remain focused until the material and learning design they want to achieve is achieved properly. good and students can receive the results of guidance from these techniques using the learning management system